2016
DOI: 10.1007/s10865-016-9722-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of need supportive text messages on motivation and physical activity behaviour

Abstract: Few short messaging service (SMS) studies to support behaviour change have used a theoretical underpinning. Using a self-determination theory perspective, we explored the effects of need supportive (NS) SMS on physical activity in 65 (BMI = 24.06 kg/m2, SD = 5.49; M = 25.76 years, SD = 10.23) insufficiently active individuals embarking on an existing exercise programme. For 10 weeks participants were randomised to an intervention group (NS) or control group (neutral). SMS were sent twice weekly, randomly, via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 53 publications
8
67
2
1
Order By: Relevance
“…A multi-theoretical framework may be needed or perhaps the text messages need to be more targeted. For example, Kinnafick et al 62 found that need-supportive text messages focused on environmental support enhanced the basic psychological needs, intrinsic motivation, and self-reported MVPA in adults. Thus, future research should investigate other methods for developing need-supportive text messages for adolescents and their effect on the basic psychological needs, intrinsic motivation, and PA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-theoretical framework may be needed or perhaps the text messages need to be more targeted. For example, Kinnafick et al 62 found that need-supportive text messages focused on environmental support enhanced the basic psychological needs, intrinsic motivation, and self-reported MVPA in adults. Thus, future research should investigate other methods for developing need-supportive text messages for adolescents and their effect on the basic psychological needs, intrinsic motivation, and PA.…”
Section: Resultsmentioning
confidence: 99%
“…Because satisfaction of the basic psychological needs promotes autonomous motivation, 28 and motivation is an essential component of behavior change, 61 SDT-informed text messages represent a potentially cost effective method for increasing PA. Further, an SDT-grounded study with inactive adults enrolled in an exercise class found that need supportive text messages increased intrinsic (autonomous) motivation and self-reported moderate-to-vigorous PA (MVPA). 62 This suggests that need-supportive text messages may be an effective method for increasing and sustaining both autonomous motivation and PA in adolescents. Thus, there is a need to investigate the feasibility and acceptability of this cost-effective, scalable, and easy to disseminate approach with adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…These studies had distinctive points in their interventions; Chen et al () facilitated the study participants to monitor their daily activity levels, whereas Thompson et al () used goal prompt text messaging developed in partnership with adolescents. Previous research suggested the importance of theoretical framework (Kinnafick, Thogersen‐Ntoumani, & Duda, ) or the incorporation of entertaining components, such as games, when targeting adolescents (Thorsteinsen, Vittersø, & Svendsen, ). Thus, further investigation is recommended to consider and incorporate diverse components that best induce the physical activity of adolescents through mobile phone intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research and existing reviews support the use of psychological theory to help identify behavioural determinants that messages can be tailored to [10,15]. This scoping review identified a number of determinants by which messages could be tailored to, namely: Stage of Change (as described in Transtheoretical Model) [10,84], social support needs [84][85][86] and self-efficacy [10,28]. The increasing potential for intervention designers to create individually tailored messages due to advancements in technology is also apparent in the evidence base [30,87].…”
Section: Message Contentmentioning
confidence: 99%